2014
DOI: 10.1007/s11481-014-9565-x
|View full text |Cite
|
Sign up to set email alerts
|

Domain Structure and Conformational Changes in rat KV2.1 ion Channel

Abstract: Voltage-gated potassium Kv2.1 channels are widely distributed in the central nervous system, specifically in neuroendocrine and endocrine cells. Their cytoplasmic C-termini are large and carry out many important functions. Here we provide the first direct structural evidence that each C-terminal part within the Kv2.1 ion channel is formed by two distinct domains (Kv2 and CTA). We expressed and purified two C-terminal truncation mutants of a rat Kv2.1 channel, lacking the entire C-termini or the CTA domain. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In this study, using variants of recombinant Kv2.1 proteins expressed in CHO cells, we report that phosphorylation events at Y124 and S800 are tightly co-dependent, and seem to be strongly influenced by putative N- and C-terminal interactions, previously proposed by Sesti and co-workers to be mediated by critical intracellular cysteine residues C73 and C710 [ 29 ], likely as a result of previously reported pro-oxidant sulfhydryl residue modification of these amino acids [ 29 , 30 ]. Although there is a gap in our knowledge regarding the structure of the very long cytoplasmic intracellular tail that is unique to Kv2 channels [ 37 , 38 ], FRET-based studies do suggest that during channel activation, segments of the N-terminal so-called T1 domain, which encompasses C73, can come in close apposition to the C-terminal activation (CTA) domain, which is a bit downstream of C710, but it does encompass S800 (CTA: residues 741–853) [ 39 ]. Importantly, truncation and immunoprecipitation based studies Mohapatra and Trimmer [ 31 ] strongly argue that there is a physical interaction between segments of the C-terminus and the N-terminus of Kv2.1.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, using variants of recombinant Kv2.1 proteins expressed in CHO cells, we report that phosphorylation events at Y124 and S800 are tightly co-dependent, and seem to be strongly influenced by putative N- and C-terminal interactions, previously proposed by Sesti and co-workers to be mediated by critical intracellular cysteine residues C73 and C710 [ 29 ], likely as a result of previously reported pro-oxidant sulfhydryl residue modification of these amino acids [ 29 , 30 ]. Although there is a gap in our knowledge regarding the structure of the very long cytoplasmic intracellular tail that is unique to Kv2 channels [ 37 , 38 ], FRET-based studies do suggest that during channel activation, segments of the N-terminal so-called T1 domain, which encompasses C73, can come in close apposition to the C-terminal activation (CTA) domain, which is a bit downstream of C710, but it does encompass S800 (CTA: residues 741–853) [ 39 ]. Importantly, truncation and immunoprecipitation based studies Mohapatra and Trimmer [ 31 ] strongly argue that there is a physical interaction between segments of the C-terminus and the N-terminus of Kv2.1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the structure of voltage‐gated potassium channels suggested the so‐called three‐dimensional “gondola” model. According to this model, the N‐ and C‐terminals of α‐subunits form the regulatory cytoplasmic subunit, in addition to the ion pore subunit that is formed by transmembrane segments that are embedded in the plasma membrane . Given the different structures of the C‐terminal of electrically‐active and KvS subunits, the content of the cytoplasmic subunit that is formed may vary.…”
Section: Structure Of Voltage‐gated Potassium Channelsmentioning
confidence: 99%
“…According to this model, the N-and C-terminals of α-subunits form the regulatory cytoplasmic subunit, in addition to the ion pore subunit that is formed by transmembrane segments that are embedded in the plasma membrane. 11,12,16,17 Given the different structures of the C-terminal of electrically-active and KvS subunits, the content of the cytoplasmic subunit that is formed may vary. This modulates properties of a channel depending on the ratio of electrically-active and KvS α-subunits in heterotetramers.…”
Section: Structure Of Voltage-gated Potassium Channelsmentioning
confidence: 99%
“…Whereas some of the effects described above might be due to K v 2.1 overexpression, we assumed that K v 2.1-mCherry subunits, which have been functionally tested by electrophysiology (see Fig. 5), would dimerize with the endogenous K v 2.1 to form the tetrameric channel structure (26).…”
Section: K V 21 Clusters Replenish Insulin Granule Fusionmentioning
confidence: 99%